The role of misperceptions in attitudes to immigration - Timmons, Shane; Fox, Celine; Carron-Kee, Evan; Murphy, Keire; Lunn, Pete (ESRI, 2026)
This study examines public perceptions of immigration in Ireland and their relationship to immigration attitudes. It was conducted against a backdrop of heightened salience of immigration in public discourse, marked by violent protests at buildings earmarked for asylum seekers, increases in racially motivated hate crimes and the spread of online misinformation. While the majority of the Irish public has maintained comparatively positive attitudes toward immigration, these events and related discourse underscore the importance of understanding the drivers of attitudes to immigration. Before presenting the findings, three contextual considerations are important to highlight. First, we did not expect individuals to know precise immigration statistics. Misperceptions of social and economic facts are common across many domains. What matters is not necessarily the accuracy of beliefs, but in how inaccuracies might relate to broader attitudes and, potentially, behaviours. Second, while we examine the relationship between misperceptions and attitudes, we do not assume that misperceptions cause attitudes. Though a causal relationship is plausible, identifying causality would require controlled experimental variation of perceptions, which is beyond the scope of this study. Nonetheless, establishing correlational relationships is a valuable step toward assessing whether causal links may exist and whether efforts to correct misperceptions may be worthwhile. Third, the purpose of this study is not to advocate for changing attitudes toward immigration for their own sake. Rather our aim was to identify systematic misperceptions that can distort democratic debate, increase vulnerability to misinformation and exacerbate social tensions. With these considerations in mind, we focused on two primary questions: (1) How accurate are public intuitions about immigration facts, such as population size, reasons for migration and migrant characteristics? (2) Are these perceptions linked to attitudes, even when accounting for other known predictors?